Edukasi Tentang Relaksasi Nafas Dalam Untuk Pengurangan Ansietas Pada Ibu Hamil Trimester III Di Klinik Juliana Harahap Tahun 2025 - Yetti Atiyah; Elvi Sepriani (STIKES Columbia Asia Medan, 2025)
Anxiety is a common psychological problem experienced by third-trimester pregnant women, particularly as they approach labor. If left unaddressed, this condition can negatively impact both maternal and fetal health. This community service activity aimed to provide education on deep breathing relaxation techniques as an effort to reduce anxiety among third-trimester pregnant women at Juliana Harahap Clinic in 2025. The methods used included lectures, direct simulation, and question-and-answer sessions supported by leaflet media, involving 20 third-trimester pregnant women as participants. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after the intervention and analyzed using the Wilcoxon Signed Rank Test. The results showed that prior to the education, the majority of respondents experienced moderate anxiety (55.0%) and severe anxiety (30.0%). Following the intervention, a significant reduction was observed, with 30.0% of respondents categorized as anxiety-free and 55.0% classified under mild anxiety, with no respondents remaining in the severe anxiety category. Statistical analysis yielded a p-value of 0.000 (p < 0.05), with a decrease in the mean anxiety score from 2.15 to 1.15. It is concluded that deep breathing relaxation education significantly reduces anxiety levels in third-trimester pregnant women and is recommended for integration into routine antenatal care service programs at healthcare facilities.